The Creative Economy-Based Advertising Language - Yustinah Yustinah; Jumai Jumai (Eduvest - Journal of Universal Studies, 2025)
This research took the theme of Creative Economy-based Advertisement Language of Economy Faculty at Universitas Muhammadiyah Semarang. This research analyzed the implementation of creative economy-based advertisement language. The research subjects were 165 students at the Economy Faculty of Universitas Muhammadiyah Semarang. Of all students, 91 students were from the undergraduate management program, 55 students from the undergraduate accounting program, 12 students from the non-regular management program, and 12 students from the non-regular accounting program. This descriptive research took the data by filling the instrument via Google form. The results showed the planning aspect with 52.47%, the implementation aspect with 53.6%, evaluation aspect with 53.3%. The results found the creative economy-based advertisement language at the faculty reached a percentage of 53.9%. The result indicated the balance between planning, implementing, and evaluating. The results were useful for the students in their complementary courses and learn autonomously.